Pengaruh Lingkungan, Stres dan Kepuasan Kerja Terhadap Kinerja Karyawan pada PT. Prakarsa Betung Meruo Jambi Senami Jambi (PBMSJ) Kecamatan Bajubang Kabupaten Batang Hari - Etty Siswati (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT STIE-GRAHA KARYA MUARA BULIAN, 2021)
This study aims to determine the effect of environment, stress and job satisfaction on employee performance at PT. Betung Meruo Jambi Initiative Jambi Senami (PBMSJ) Bajubang District, Batang Hari Regency. This type of research is research with quantitative data types. Sources of data in this study came from primary data and secondary data. The sample of this study was 60 respondents who were taken by survey, namely research that used a questionnaire as a research instrument. The method of analysis and the data uses a validity test, with a Liker scale approach. Based on the results of the tests carried out. From the results of the data validity test that r count > r table of each variable Environment (X1), Stress (X2), Job Satisfaction (X3), explains that from several statements each variable is declared valid. There is the influence of work environment on employee performance, there is the effect of work stress on employee performance, there is the effect of job satisfaction on employee performance, there is the influence of work environment, job stress, job satisfaction on employee performance at PT. Prakarsa Betung Meruo Senami Jambi with an index of 2.77.